IMPLEMENTASI SISTEM INFORMASI MANAJEMEN UNTUK MENUNJANG PELAYANAN ADMINISTRASI PADA SEKOLAH MENENGAH KEJURUAN NEGERI 1 KOTA PADANGSIDIMPUAN - Wawan Patriansyah; Nurbaya Harianja; Rina Tiur Lona (Universitas Pahlawan Tuanku Tambusai, 2022)
Technological developments require the world of education, especially schools to implement management information systems in supporting administrative services, both for students, teachers, education staff, as well as for the completeness of appropriate infrastructure. The purpose of this study was to find out how the process of administrative services through the implementation of management information systems at SMK Negeri 1 Kota Padang Sidempuan. In carrying out this research, qualitative methods were used through literature studies and field studies to be able to collect sufficient data. Furthermore, the data was analyzed through stages such as simplifying the data to determine the research focus, compiling research reports, and drawing conclusions according to the research objectives. The research data were obtained through interviews, observation, and questionnaires. From this study, the results were obtained that implementing a management information system could support administrative services at SMK Negeri 1 Kota Padang Sidempuan. Implementation of this management information system has been running effectively and efficiently. Utilization of facilities and infrastructure is appropriate and optimal so that the quality of education at SMK Negeri 1 Padang Sidempuan City is increasing along with the increase in administrative service processes and being able to help students, teachers and other employees in learning process activities and easier to obtain the latest information. Keywords: Implementation, Management Information System, Service Administration